Enhancing First-Year English Education Students’ Speaking Skills through Storytelling Training at State University of Makassar - Wahyuni, Ika Yuli; Ariyani, Amra; Sakkir, Geminastiti; Amaliah, Suci; Mansyur, Mansyur (PT ARRUS Intelektual Indonesia, 2025)
This study investigates the effectiveness of storytelling training in enhancing the speaking skills of first-year students in the English Education Program at Universitas Negeri Makassar. The research was motivated by a survey of senior students, which revealed that 15.8% were still at the A1 level and 35.3% at the A2 level of the CEFR, indicating persistent challenges in speaking confidence and performance, particularly in formal academic contexts. The study involved 14 participants selected randomly to represent each first-year class. Data were collected through a post-training perception survey using closed-ended questionnaires covering aspects of fluency, pronunciation, vocabulary, comprehension, clarity, and speaking confidence. The results showed that all participants perceived improvements in their speaking abilities, with the highest agreement (100%) observed in vocabulary, comprehension, and confidence, followed by pronunciation (92.9%), clarity (92.9%), and fluency (85.7%). These findings suggest that storytelling can serve as an effective strategy for improving both the linguistic and affective aspects of speaking in EFL contexts. The study concludes that storytelling is a valuable pedagogical tool that should be integrated into the early stages of English language teacher education.